Proposals for the Second Five Year Plan Ex-Criminal Tribes Vol. No. IV Government of Madhya Bharat - Planning Commission (Planning Commission, 1955)
The Ex-Criminal Tribes are spread through. Madhya Bharat. The Welfare Activities for their reclamation wild be required to be arranged in Majority of Districts, it is therefore essential that an experienced officer is appointed to be directly in charge of those activities. It is therefore, proposed that a post of Assistant Director in charge of the welfare of Ex-Criminal Tribes should be advocated and the staff as mentioned in the budget examined is proposed.
Government of Madhya Bharat